The Use of Tobacco Extract as an Environmentally Friendly Corrosion Inhibitor in the Protection of Steel Pipes in the Soil: - Ali, Zainab H.; Abbass, Muna K.; Kassim, Muthana M.; Sadalden, Mahmood M. (Journal of Petroleum Research and Studies, 2025)
The research aims to solve the problem of corrosion in oil pipes buried in the soil by studying the addition of tobacco extract on the rates of corrosion of low carbon steel in a solution that simulates the soil conditions. The corrosion solution used is an aqueous solution that simulates soil conditions and pH of the solution was pH = 6.8 at 30◦C samples of low carbon steels were used, which are used in the petroleum industries. In this research, the Tafel polarization method was carried out in Tobacco extract solution using Potentiostat device was used to measure corrosion parameters: corrosion potential, corrosion current, Tafel slopes and corrosion rates of all samples for the purpose of knowing the inhibition efficiency and completing the corrosion cell calculations. It was found that the samples coated with tobacco dust have lower corrosion currents than that of uncoated base (blank sample) at all month starting from June to November, but the coated samples have the lowest corrosion rate on June month (after 60 days’ immersion in soil), the corrosion rate was 0.02237 mpy as comparison to as received blank 5.6168 mpy with inhibition efficiency 99.6%. But it becomes 3.2083 mpy on November month with inhibition efficiency 42.88% on November month because formation of a protective layer on the steel surface, it reduces the corrosion rate due to the absorption of water and the chloride ions.